(untitled) (Bangladesh Journal of Microbiology, 2008)
In the present study three mesophilic Bacillus isolates were analyzed for their α-amylase activity in shakeflask cultures. The organisms were capable to produce hydrolysis zone around their colonies on starch agar medium. The effect of various fermentation conditions on α-amylase production was investigated, and in every case it was found that B. subtilis was the best producer of the enzyme, which was followed by the newly isolated Bacillus sp. and B. amyloliquefaciens. The synthesis of extracellular α-amylase by the bacteria was repressed by the presence of readily metabolizable carbon source like glucose in the culture medium. Maximum α-amylase activity by the Bacillus isolates was obtained at 37°C with an initial medium pH 7.0 under agitation at 160-180 rpm for 72 h of growth. Keywords: Bacillus species, α-Amylase, Enzyme production, Shake-flask culture DOI: http://dx.doi.org/10.3329/bjm.v24i2.1257 Bangladesh J Microbiol, Volume 24, Number 2, December 2007, pp 129-132